Research with Indigenous Girls: A Review - Campbell, Jessica (Contemporary Kanata: Interdisciplinary Approaches To Canadian Studies, 2025)
This review explores decolonial research methodologies for engaging Indigenous adolescent girls, focusing on mitigating colonial legacies within research practices. Critically examines existing literature and highlights the imperative of centring Indigenous perspectives and knowledge production while decentering Western academic paradigms. This review underscores the importance of collaboration with participants by drawing on examples from participatory and land-based research methods, such as arts- based activities and photovoice. Further, there is the need for research to be reciprocal and beneficial to participants, fostering meaningful relationships and prioritizing authentic engagement. Barriers to participation, including paternalistic consent requirements, challenges in disseminating data, and strategies to address these obstacles are identifiable. While the review focuses on the experiences of Indigenous adolescent girls 13 to 18 years old, it also calls attention to the need for inclusive research practices that engage younger Indigenous children. The review offers insights into decolonial methodologies that prioritize Indigenous knowledge and empower participants, contributing to more ethical and equitable research practices.